Lifting and transportation in high-rise building construction in Japan: the beginning of integrated lifting and transportation and recent developments. Issue 5 (2nd September 2020) - Gondo, Tomoyuki; Miura, Reiji; Kurosaka, Masato
ABSTRACT: Lifting and transportation (LT) directly affects construction costs and timetables for high-rise buildings. Recently in Japan, the occupation of professional lifting and transportation subcontractor (PLTS) was established, and the LT construction system has evolved into an integrated lifting and transportation (ILT) system. In the ILT system, PLTSs (rather than general contractors) manage the entirety of LT during construction. However, this change in LT systems since the beginning of high-rise building construction has not been investigated. For the improvement of LT management or productivity, this study aims to clarify the development process of LT and explore recent developments and problems in ILT in high-rise building construction via literature surveys, interviews, questionnaires, and surveys on construction sites. The findings are as follows: First, following an increase in workers' wages in the 1990s, several PLTSs started working exclusively on LT, and during the 2000s, PLTSs began to manage all LT on construction sites. Second, most PLTS companies are small and have difficulty training workers, and the scope of LT work is not clear. Third, this paper clarifies the types of LT and several LT problems found on construction sites that are caused by a lack of communication between general contractors and PLTSs.